Oxford concise colour medical dictionary / Elizabeth A Martin - Martin, Elizabeth A
This practical medical dictionary contains over 12,400 entries, fully revised and updated to include the very latest developments in this fast-changing field. Informative and accessible, with a clear two-colour text design, this bestselling title is essential for medical students and professionals, and for anyone seeking a home medical guide